Introduction: Gendering Social Movements and Everyday Activism - Fabian, Louise; Yung Nielsen, Louise (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This special issue of Conjunctions bears the title Feminism, Gender, Social Movements and Everyday Resistance. This introduction will analyse chosen relations between these four phenomena, amongst others by showing how feminism and women’s movements have made a substantial impact on different societies and cultures all over the world and have inspired the protest repertoires and analytical frameworks of both social movements and more informal forms of everyday resistance. The introduction introduces, explores and links the intersectional turn in feminism, different theories of everyday resistance and the role of culture in politics and resistance. After mapping out this more general theoretical landscape of gendered activism, the introduction introduces and reflects on a number of the recurring themes in the contributions to this special issue. These themes are ‘mediatised activism’, ‘mobilisation of affect’, ‘online misogyny and reactionary movements of the far right’, ‘the body as a political site’ and ‘citizenship and the rights to have rights’. By showing how feminism and feminist theory have developed over time through different movements, actors and different forms of activism working to promote more equal political, cultural, social and economic rights and opportunities for all genders, the introduction also raises more fundamental questions about the relationship between theory and activism. Amongst others it shows that the way we define and understand politics and what we recognise and acknowledges as politics is in itself a political act and an important part of the politics of knowledge construction.